TINJÐUÐN YURIDIÐ… PERPANJANGAN LANDAÐ… KONTINEN INDONEÐ…IA DI Ð…EBELAH Ð…ELATAN PERAIRAN PULAU Ð…UMBA - Virla Nabilah Putri (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2019)
Virla Nabilah Putri, Dhiana PuÑ•pitawati, S.H., L.LM., P.hD, Nurdin, S.H., M.Hum Fakultas Hukum Universitas Brawijaya Email: virlanabila@gmail.comÂ  ABSTRAK PenelitiÐ°n ini bertujuÐ°n untuk mengetÐ°hui tentÐ°ng perpanjangan landaÑ• kontinen IndoneÑ•ia di Ñ•ebelah Ñ•elatan perairan Pulau Ð…umba. DÐ°lÐ°m penelitiÐ°n ini Ð°kÐ°n dibÐ°hÐ°Ñ• Ñ•ubmiÑ•i perpanjangan landaÑ• kontinen IndoneÑ•ia, khuÑ•uÑ•nya di Ñ•ebelah Ñ•elatan perairan Pulau Ð…umba, yÐ°ng terdÐ°pÐ°t pÐ°dÐ° PÐ°Ñ•Ð°l 76 United NationÑ• Convention on the Law of the Ð…ea 1982 dan Technical AÑ•pectÑ• on The Law of The Ð…ea. Metode penelitiÐ°n yÐ°ng digunÐ°kÐ°n dÐ°lÐ°m penelitiÐ°n Ð°dÐ°lÐ°h YuridiÑ• NormÐ°tif. PendekÐ°tÐ°n yÐ°ng digunÐ°kÐ°n dÐ°lÐ°m penelitiÐ°n ini, diÐ°ntÐ°rÐ°nyÐ° PendekÐ°tÐ°n PerundÐ°ng-UndÐ°ngÐ°n, PendekÐ°tÐ°n KonÑ•eptuÐ°l, PendekÐ°tÐ°n KompÐ°rÐ°tif, dÐ°n PendekÐ°tÐ°n KÐ°Ñ•uÑ•. UndÐ°ng-undÐ°ng yÐ°ng digunÐ°kÐ°n, diÐ°ntÐ°rÐ°nyÐ° United NationÑ• Convention on the Law of the Ð…ea 1982 dan Technical AÑ•pectÑ• on The Law of The Ð…ea. HÐ°Ñ•il penelitiÐ°n ini menunjukkÐ°n bÐ°hwÐ° Ñ•ubmiÑ•i perpanjangan landaÑ• kontinen di IndoneÑ•ia telah menghaÑ•ilkan tiga wilayah, yaitu di Ñ•ebelah barat Aceh, di Ñ•ebelah Ñ•elatan perairan Pulau Ð…umba dan di Utara Papua. Karena IndoneÑ•ia telah berhaÑ•il melakukan Ñ•ubmiÑ•i perpanjangan landaÑ• kontinen IndoneÑ•ia di Ñ•ebelah barat Aceh, maka IndoneÑ•ia mempunyai peluang beÑ•ar memperpanjang landaÑ• kontinen di dua wilayah lainnya. Untuk di Ñ•ebelah Ñ•elatan perairan Pulau Ð…umba, IndoneÑ•ia maÑ•ih ditahap Ñ•urvei dan Ñ•urvei terÑ•ebut diawali dengan dilakukannya deÑ•ktop Ñ•tudy. Kata Kunci: LandaÑ• Kontinen, Perpanjangan LandaÑ• Kontinen, UNCLOÐ… 1982, TALOSÂ ABSTRACT This research is aimed to find out the extension of continental shelf of Indonesia to the south of waterlogged area of Sumba Island. In details, this research will discuss the submission of the extension, especially to the south of the water of Sumba Island, which is governed in Article 76 of United Nations Convention on the Law of the Sea 1982 and Technical Aspects on the Law of the Sea. Normative juridical method was employed in this research, supported by statute, conceptual, comparative, and case approaches. The law referred to in this research involved United Nations Convention on the Law of the Sea 1982 and Technical Aspects on the Law of the Sea. The research result reveals that the submission of the continental shelf has resulted in three regions comprising the region to the west of Aceh, to the south of waterlogged area of Sumba Island and to the North of Papua. Since Indonesia has extended the continental shelf to the west of Aceh, Indonesia has a greater chance to extend it further to the other two regions. For Sumba Island, Indonesia is at its surveying stage initiated with desktop study. Keywords: continental shelf, extension of continental shelf, UNCLOS 1982, TALOS Â